The Influence of Workload, Change Management, and Sense of Belonging on Personnel Performance at the East Java Regional Police Inspectorate - Kanti, Ati Nurmi; Rahayu, Sri; Suharto, Babun; Fitrianty, Rifda (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study investigates the effects of workload, change management, and sense of belonging on personnel performance at the East Java Regional Police Inspectorate. The increasing complexity of policing in the digital era requires internal oversight units to maintain high performance while adapting to organizational change and managing escalating task demands. This research employed a quantitative explanatory design using a census approach, involving 46 personnel as respondents. Primary data were collected through a structured questionnaire measured on a five-point Likert scale. Data were analyzed using multiple linear regression with the support of SPSS 25.0. The results indicate that workload has a negative and significant effect on personnel performance, suggesting that excessive task demands may reduce work effectiveness. In contrast, change management and sense of belonging have positive and significant effects on performance, demonstrating that structured organizational change and strong psychological attachment to the organization enhance personnel outcomes. Simultaneous testing confirms that workload, change management, and sense of belonging jointly exert a significant influence on personnel performance, with the model explaining 85.7% of performance variance. These findings highlight that personnel performance in an internal police oversight context is shaped by the interaction of operational pressure, organizational adaptability, and psychological factors. The study contributes to the human resource management and organizational behavior literature by providing empirical evidence from a law enforcement oversight setting and offers practical insights for improving performance through balanced workload management, effective change strategies, and the cultivation of a strong sense of belonging among personnel.